A three-month physical training program improves cardiovascular autonomic function in patients with metabolic syndrome with and without diabetes – a pilot study - Vágvölgyi, Anna; Ábrahám, Judit Erzsébet; Máthéné Köteles, Éva; Korom, Andrea; Barnai, Mária; Szűcs, Mónika; Orosz, Andrea; Kempler, Péter; Menyhárt, Adrienn; Nemes, Attila; Várkonyi, Tamás; Baczkó, István; et al. (Frontiers in Endocrinology, 2023)
Introduction: Vascular complications and neuropathy may develop in the presence of metabolic syndrome. The aim of our study was to measure the cardiovascular autonomic function following physical training in patients with metabolic syndrome with and without diabetes. Subjects and Methods: 56 patients with metabolic syndrome (32 men/24 women, 40 non-diabetic patients (NDMetS)/ 16 diabetic patients (DMetS) [mean ± SD]: age: 50.35±8.03 vs. 56.8±9.30 years, p=0.023; baseline BMI: 32.2±7.03 vs. 32.8±5.94 kg/m2, p=0.739) were involved in our study. All tests and measurements were carried out before and following a 3-month physical training period. Autonomic function was assessed by means of five standard cardiovascular reflex tests. ECG repolarization parameters, including short-term QT variability and stress-ECG were also measured. Results: In the whole population, Valsalva-ratio (VR) and the autonomic score (AS) improved following training (VR: 1.49±0.24 vs. 1.64±0.34, p=0.001; AS: 2.05±1.73 vs. 1.41±1.36, p=0.015) accompanied by the significant decrease of the systolic (150.3±16.12 vs. 134.1±16.67 mmHg, p<0.001) and diastolic (90.64±12.8 vs. 82.79±11.1 mmHg, p<0.001) blood pressure. An improvement in VR was detected in NDMetS patients following training (1.51±0.24 vs. 1.67±0.31, p= 0.002). No significant changes could be detected in autonomic tests’ results in the DMetS patient group following training. The applied exercise training program did not lead to significant changes in ECG repolarization. The stress-ECG test in the whole study population yielded a significant increase in the test duration (12.9±3.76 vs. 15.1±2.96 min, p<0.001) and in the test load (10.5±2.78 vs. 11.6±2.39 MET, p<0.001). The load capability improved significantly in both subgroups: 11.1±2.04 vs. 12.1±1.82, (p<0.001) and 9.0±3.64 vs. 10.4±3.05, (p=0.033) in subpopulations of NDMetS and DMetS, respectively. The DMetS patients achieved a significantly lower MET score at baseline (p=0.039) and following training (p=0.044) in comparison to the NDMetS patients. Conclusions: The three-month exercise program improved the Valsalva-ratio and the AN score in the MetS patients, that is potentially protective against cardiovascular events. The training had some beneficial effect on blood pressure and the results of the stress-ECG tests in both groups. The absence of significant change in the reflex tests in DMetS group reflects an impaired adaptation compared to the NDMestS group.